CT-diagnosed emphysema and prognosis of chronic airflow obstruction: a retrospective study. Issue 11 (4th November 2013) - Kurashima, Kazuyoshi; Fukuda, Chiaki; Nakamoto, Keitaro; Takaku, Yotaro; Hijikata, Naoya; Hoshi, Toshiko; Kanauchi, Tetsu; Ueda, Miyuki; Takayanagi, Noboru; Sugita, Yutaka; Araki, Ryuichiro
Abstract : Objective: CT-diagnosed emphysema is associated with poor prognosis in chronic obstructive pulmonary disease (COPD). Its clinical impacts on prognoses of asthma with chronic airflow obstruction (CAO) are not well known. We sought to compare mortalities and prognostic factors in COPD and asthma with CAO by the presence or absence of CT-diagnosed emphysema. Design: Retrospective cohort study. Setting: Referral centre hospital for respiratory disease. Participants: 1272 patients aged over 40 years with CAO (January 2000 to December 2011). CAO was defined as a forced expiratory volume in 1 s/forced vital capacity <0.7 after bronchodilator use throughout the observation period. Primary and secondary outcome measurements: Overall mortality served as the primary endpoint. We compared mortalities and prognostic factors of COPD and asthma subgroups with or without emphysema. Secondary endpoints were the prevalence of COPD and asthma in patients with CAO. Results: Overall, diagnoses included COPD with emphysema in 517 (40.6%) patients, COPD without emphysema in 104 (8.2%) patients, asthma with emphysema in 178 (13.9%) patients, asthma without emphysema in 169 (13.3%) patients, other respiratory diseases (RD) with emphysema in 128 (10.1%) patients, and other RD without emphysema in 176 (13.8%) patients. Patients with asthma without emphysema had the best prognosis followed by those with asthma with emphysema, COPD without emphysema and COPD with emphysema. Each subgroup had distinct prognostic factors. Presence of emphysema was an independent risk factor for de novo lung cancer among patients with CAO. Conclusions: Patients with asthma with CAO have a better prognosis than patients with COPD. The presence of CT-diagnosed emphysema predicts poor prognosis in COPD and asthma with CAO.